2014
DOI: 10.1159/000368471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paricalcitol and Aliskiren Combination Therapy on Experimental Diabetic Nephropathy Model in Rats

Abstract: Background/Aims: The aim of the present study was to investigate the effect of combination of aliskiren with paricalcitol on experimental diabetic nephropathy (DN) model in rats. Methods: Forty male Sprague Dawley rats were divided into 5 groups of 8 rats each, namely the control (Group C), diabetes (Group D), aliskiren (Group A), paricalcitol (Group P), and aliskiren plus paricalcitol (Group A+P) groups. Aliskiren was given by oral-gavage at a dose of 50 mg/kg/day once daily for 12 weeks. Paricalcitol was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Furthermore, paricalcitol has been shown to attenuate contrast-induced nephropathy by suppression of renal and systemic oxidative stress. 8 Eren et al 9 also recently reported that paricalcitol improves albuminuria and intrarenal oxidative stress in diabetic rats. These findings that address the pleiotropic effects of paricalcitol and our findings suggest that paricalcitol may well have benefits in the chronic as well as acute settings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, paricalcitol has been shown to attenuate contrast-induced nephropathy by suppression of renal and systemic oxidative stress. 8 Eren et al 9 also recently reported that paricalcitol improves albuminuria and intrarenal oxidative stress in diabetic rats. These findings that address the pleiotropic effects of paricalcitol and our findings suggest that paricalcitol may well have benefits in the chronic as well as acute settings.…”
Section: Discussionmentioning
confidence: 94%
“…[5][6][7] Recently, it has been shown that paricalcitol has anti-oxidant effects on renal tissue and suppresses the reninangiotensin system (RAS) in diabetic kidney. 8,9 Fryer et al 10 demonstrated that paricalcitol suppresses renal renin expression. It has also been recently reported that the combination of paricalcitol and enalapril treatment ameliorates oxidative injury by suppressing reactive oxygen species generating enzyme NADPH oxidase activity and by up regulating the antioxidant defense system in a uremic rat model of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…[152] Low level of vitamin D are linked to diabetic nephropathy [153] Vitamin D receptor activator such as paricalcitol is found to be interesting. [154] Paricalcitol 1) Reduces proteinuria in diabetic patient [155] 2) Reconfirmed in VITAL study-albuminuria was reduced instead of proteinuria [157] 3) Combination with aliskiren can reduce progression of diabetic nephropathy [158] 4) Addition of adequate RAAS blocker is necessary 5) Calcitriol also have same effect [159] …”
Section: ] Vitamin D Receptor Activator [152-159]mentioning
confidence: 99%
“…klotho also exerts inhibitory action on renal fibrosis and cardio-vascular atherosclerosis in high oxidative stress conditions such as hyperglycemia and DM ( [41] showed that vitamin D/VDR signaling in podocytes plays a critical role in the kidney protection from diabetic injury and reconstitution of VDR null mice with the human VDR (hVDR) transgene in podocytes rescued the severe diabetes-related renal damage. Experimental studies showed that administration of a selective vitamin D analogue like Paricalcitol reduces albuminuria [42].…”
Section: Iron and Oxidative Stressmentioning
confidence: 99%
“…Recently a review by Mary Choi and her group [42] showed that the accumulation of damaged proteins and organelles is associated with the pathogenesis of DN. Autophagy pathway in the kidney is activated under high glucose conditions, with increased oxidative stress via free radicals in PCT cells, and in podocytes.…”
Section: Autophagymentioning
confidence: 99%